PENINGKATAN HASIL BELAJAR PENDIDIKAN JASMANI MELALUI PENERAPAN METODE DEMONSTRASI DAN TEKNIK DRILL KELAS VIIA SMP NEGERI 6 MATARAM TAHUN PELAJARAN 2022/2023 - I GUSTI NYOMAN SAPTARI (GANEC SWARA, 2023)
This study aims to find out: (1) Improving physical education learning outcomes by applying the demonstration method and drill techniques for Class VIIA students of SMP Negeri 6 Mataram for the 2022-2023 academic year. (2) The effectiveness of applying the demonstration method and drill techniques in improving physical education learning outcomes class VIIA students of SMP Negeri 6 Mataram for the 2022/2023 academic year. The study used a classroom action research design including planning, acting, observing, and reflecting components. The research subjects were class VIIA students at Mataram 6 Public Middle School, with a sample of 38 people, consisting of 20 male students and 18 female students. The research variables consist of 2 (two) parts (1) the action variable, namely the application of demonstration methods and drill techniques, and (2) the expectation variable, namely the learning outcomes of sports and health physical education (PJOK). Data collection techniques used written tests to find out learning outcomes in the realm of knowledge, and practical tests to find out learning outcomes in the skills domain, while to find out the results of the implementation of learning using observations from 2 (two) observers. Data analysis techniques use percentages. From the results of the study it was concluded that the demonstration method and drill techniques can improve the learning outcomes of physical, sports and health education in Class VIIA Mataram 6 Public Junior High School in the 2022/2023 academic year. I 71.05% cycle II 78.95% and cycle III 89.47%.